Muscle fatigue in swimming - Rouard, A. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Fatigue is a complex phenomen defined as an acute impairment of performance. In swimming, few studies are done on biomechanical parameters of fatigue. A review on the effects of fatigue on muscle in swimming is presented. METHODS: Muscular activations were detected from surface or fine wires electrodes. Raw EMG`s are full wave rectified, integrated (IEMG) and normalised to quantify the degree of muscle activation. The frequency process is based upon Fourier transform and time-frequency treatments. RESULTS: and DISCUSSION: IEMG decreased for the most sollicitated muscles (M. Deltoideus or M. Flexor carpi)(Wakayoshi et al, 1994) and increased for muscles with submaximal contractions (M int. or ext. rotators) (Monteil,1996). A shift of spectral parameters of the EMG`s of the M. biceps and triceps brachii toward lower frequency was observed during maximal voluntary contractions (MVC) realised before and after an exhaustive test (Aujouannet et al, 2006) when a derive of the instantaneous mean frequency (MNF) was noted for the M. antagonist Flexor and Extensor carpi during the swimming test (Caty et al,2006). These changes were associated to decrease in force productions either for the maximal dry strength or to the maximal tethered force or to the maximal power (Rouard et al, 2006). More, the hand path changed with a greater duration of the catch phase, a shorter insweep (Aujouannet et al, 2006) and a decrease in hand velocity (Monteil, 1996). EMG methods allowed resolving individual strategies of swimming and adjustments caused by fatigue. Future investigations will be required to evaluate the load-sharing across muscles and/or to determine the central or peripheral components of the fatigue in swimming. REFERENCES: Aujouannet, Y. et al. (2006). Effects of a high intensity swim test on kinematic parameters in high-level athletes. Applied Physiology, Nutrition and Metabolism, 31, 150-158 Monteil,K.M.et al. (1996) Swimmers`shoulder: EMG of the rotators during a flume test. In: Biomechanics and Medicine in Swimming VII., 83-89.Rouard, A.H. et al. (2006). Isometric force, tethered force and power ratios as tools for the evaluation of technical ability in freestyleswimming. In Biomechanics and Medicine in Swimming X, 249-250. Wakayoshi K, et al. (1994) Electromyographyc evidence of selective muscle fatigue during competitive swimming.